Pengaruh Metode Bercerita terhadap Komunikasi Dua Arah pada Anak Keterlambatan Bicara (Speech Delay) Usia 4 Tahun - Arrum Wulan Alfurqoni; Lailil Aflahkul Yaum; Asrorul Mais (JOEAI (Journal of Education and Instruction), 2026)
This study aimed to determine the effect of storytelling on improving two-way communication and to analyze changes in these skills before and after intervention. The method used was quantitative, using a Single Subject Research (SSR) approach with an A–B design. The results showed significant improvement, with scores increasing from 8–9 in the baseline phase to 18–22 in the intervention phase, accompanied by a positive trend, high stability, and no overlap between phases. In conclusion, storytelling has proven effective in improving two-way communication skills in children with speech delay.   Keywords: Storytelling Method; Two-Way Communication; Speech Delay